Performance Enhanced Ultrasound Probe Tracking With a Hemispherical Marker Rigid Body - Cai, Qianqian (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2021)
Among tracking techniques applied in the 3-D freehand ultrasound (US), the camera-based tracking method is relatively mature and reliable. However, constrained by manufactured marker rigid bodies, the US probe is usually limited to operate within a narrow rotational range before occlusion issues affect accurate and robust tracking performance. Thus, this study proposed a hemispherical marker rigid body to hold passive noncoplanar markers so that the markers could be identified by the camera, mitigating self-occlusion. The enlarged rotational range provides greater freedom for sonographers while performing examinations. The single-axis rotational and translational tracking performances of the system, equipped with the newly designed marker rigid body, were investigated and evaluated. Tracking with the designed marker rigid body achieved high tracking accuracy with 0.57° for the single-axis rotation and 0.01 mm for the single-axis translation for sensor distance between 1.5 and 2 m. In addition to maintaining high accuracy, the system also possessed an enhanced ability to capture over 99.76% of the motion data in the experiments. The results demonstrated that with the designed marker rigid body, the missing data were remarkably reduced from over 15% to less than 0.5%, which enables interpolation in the data postprocessing. An imaging test was further conducted, and the volume reconstruction of a four-month fetal phantom was demonstrated using the motion data obtained from the tracking system